Determination of Optimal HOMA-IR Cut-off Value for Identifying Insulin Resistance in a Tertiary Care Hospital, Bangladesh (Sir Salimullah Medical College Journal, 2026)
Background: Insulin resistance (IR) is a key predictor of metabolic syndrome and type 2 diabetes mellitus. HOMA-IR is widely used to assess IR, but cut-off values vary across populations. This study aimed to determine the optimal HOMA-IR cut-off for Bangladeshi adults. Methods: A cross-sectional analytical study was conducted on 1,250 adults from BSMMU outpatient department. Anthropometric measurements, blood pressure, fasting glucose, insulin, triglycerides, and HDL-C were measured. HOMA-IR was calculated using HOMA2 calculator. Optimal cut-off values were determined using percentile and metabolic syndrome criteria, and ROC curve analysis. Results: Median HOMA-IR was 1.6 (IQR: 1.1– 2.3) for the total population, 1.5 for males and 1.7 for females. The 75th percentile was 2.2 overall, higher in females. ROC analysis using metabolic syndrome criteria yielded an optimal HOMA-IR cut-off of 1.4 for the total population (AUC: 0.641, p